Qris payment flexibility and the security of transactions on purchase choices in electronic commerce and supermarkets - Tullah, Baiq Ahadia; Naim, Muhammad (Institute of Computer Science (IOCS), 2024)
The objective of this research is to examine the influence of QRIS payment flexibility and the security of transactions on purchase choices in electronic commerce and supermarkets. This research adopts a quantitative approach using a survey method, involving 88 respondents consisting of 27 males and 61 females. The research instrument is a Likert scale questionnaire with 18 items. Data were examined through the application of multiple linear regression analysis. The findings of the analysis indicate that the R Square value is 0.603, indicating that 60.3% of the variation in purchasing decisions can be explained by QRIS payment flexibility and transaction security. The ANOVA F value of 64.421 with a significance value of <0.001 indicates that the regression model used is significant. These findings imply that QRIS payment flexibility and transaction security collectively exert a notable impact on purchasing decisions within e-commerce or supermarkets. This also underscores that QRIS payment flexibility and transaction security are crucial factors affecting consumer buying choices on e-commerce platforms or in supermarkets